1999
DOI: 10.1103/physrevb.59.6058
|View full text |Cite
|
Sign up to set email alerts
|

Structural transformations in a simple-hexagonal Hg-Sn alloy under pressure

Abstract: The structure of Sn alloyed with Hg ͑10 at. %͒ was studied under pressure up to 66 GPa with energydispersive x-ray diffraction using synchrotron radiation. The ambient pressure simple hexagonal (hP1) phase transformed at 15 GPa to a body-centered tetragonal (tI2) phase similar to the high-pressure forms of Sn and InBi. The axial ratio, c/a, of the tI2 phase increased with pressure up to a maximum value of c/aϷ0.92 at about 40 GPa and remained nearly constant upon further compression to 55 GPa. At pressures abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 30 publications
8
39
0
Order By: Relevance
“…Moreover, the determination of more complicated atomic patterns has not only filled some hitherto unexplored white spots on the map of crystal structures, but also substantiated deviations from general systematic trends due to electronic alterations at reduced volumes for alkali and alkaline-earth metals. The observation of a crystal-chemical differentiation of physically identical atoms in several complex high-pressure modifications has encouraged renewed interest in the properties of compressed binary alloys [108][109][110][111][112][113][114][115][116][117]. Future work will show if the more detailed and essentially deepened working knowledge of atomic arrangements at high pressures will turn into a tool for tailoring new compounds with novel properties and shed light on the interplay of variations caused by tuning the state variables pressure and composition simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the determination of more complicated atomic patterns has not only filled some hitherto unexplored white spots on the map of crystal structures, but also substantiated deviations from general systematic trends due to electronic alterations at reduced volumes for alkali and alkaline-earth metals. The observation of a crystal-chemical differentiation of physically identical atoms in several complex high-pressure modifications has encouraged renewed interest in the properties of compressed binary alloys [108][109][110][111][112][113][114][115][116][117]. Future work will show if the more detailed and essentially deepened working knowledge of atomic arrangements at high pressures will turn into a tool for tailoring new compounds with novel properties and shed light on the interplay of variations caused by tuning the state variables pressure and composition simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Si mil ar tetra gona l di storti on of b cc ha s b een observed under pressure i n the i soel ectro ni c comp ound InBi , wi th the sam e axi al rati o [3]. The dashed l i ne i n Fi g. 7 extendi ng fro m thi s p oint at n = 4 towards l ower el ectro n concentra ti on represents tetra gonal di sto rti ons f or b ct i n the Sn-ri ch al l oys wi th In and Hg under pressure [4,5,7].…”
Section: T He In{bi Al L Oy Syst Emmentioning
confidence: 99%
“…The axi al ra ti o decreases wi th a decrease i n al l oy electro n concentra ti on. The possibl e expl anati on of thi s correl ati on shoul d b e accounted for by Bri l l oui n-zone{ Fermi-sphere Ùtti ng s di scussed i n pap ers [3,4].…”
Section: T He Sn-based Bi Nar Y Al L Oys Wi T H In and Hgmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Thus it is unlikely that the CsV structure will occur in In-stabilized Sn alloys. Degtyareva et al 19 have carried out high-pressure EDXRD measurements on the alloy Hg 0.1 Sn 0.9 using synchrotron radiation. They found that the ambient ph phase transformed at 15 GPa to a bct phase similar to the high-pressure forms of Sn.…”
mentioning
confidence: 99%